2010
DOI: 10.1111/j.1095-8649.2010.02802.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of egg distribution and geographic changes in the spawning habitat of the Brazilian sardine Sardinella brasiliensis

Abstract: This paper establishes the spawning habitat of the Brazilian sardine Sardinella brasiliensis and investigates the spatial variability of egg density and its relation with oceanographic conditions in the shelf of the south-east Brazil Bight (SBB). The spawning habitats of S. brasiliensis have been defined in terms of spatial models of egg density, temperature-salinity plots, quotient (Q) analysis and remote sensing data. Quotient curves (Q(C)) were constructed using the geographic distribution of egg density, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 35 publications
6
30
0
4
Order By: Relevance
“…The diet varies according to prey availability, which is conditioned by area and season (Goitein, 1978;Schneider & Schwingel, 1999;Kurtz & Matsuura, 2001). The productivity of the SEBB affects the development of the fish, primarily in the larval phase (Matsuura, 1996;Jablonski & Legey, 2004Gigliotti et al, 2010, Moraes et al, 2012. Productivity is more pronounced primarily during spring and summer, consistent with our results and environmental conditions (CARTON-GIESE SODA, 2013).…”
Section: Variablessupporting
confidence: 78%
“…The diet varies according to prey availability, which is conditioned by area and season (Goitein, 1978;Schneider & Schwingel, 1999;Kurtz & Matsuura, 2001). The productivity of the SEBB affects the development of the fish, primarily in the larval phase (Matsuura, 1996;Jablonski & Legey, 2004Gigliotti et al, 2010, Moraes et al, 2012. Productivity is more pronounced primarily during spring and summer, consistent with our results and environmental conditions (CARTON-GIESE SODA, 2013).…”
Section: Variablessupporting
confidence: 78%
“…However, we contend that the quality of the spawning habitat and the interannual catch variability are likely to be a consequence of specific oceanatmosphere linkages rather than the sole choice of a stable environment. There is strong evidence indicating that the spawning habitat expands and contracts along the SBB according to the interannual variability of the horizontal and vertical mesoscale structure of the ocean (Gigliotti et al, 2010). Also, our results on wind stress, Ekman transport and mixing index show a better representation of the contrasts between the southern and northern SBB sectors (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Following a physical reasoning proposed in a numerical study performed by Chaves and Nobre (2004), the increased cloudiness (Fig. 6e) in the region is likely to be the cause of the ob- Gigliotti et al (2010) demonstrated that the spawning habitat of the Brazilian sardine expands over the SBB when the SSTA during the spawning period is zero or slightly negative, leading to increased sardine catches in the following year. In contrast, the spawning habitat contracts when SSTA is positive, leading to reduced sardine catches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that this decline is related to overfishing of the Brazilian sardine population (Cergole et al, 2002). However, some studies showed that, besides overfishing, the interannual variation of the Brazilian sardine landings may be partially related to climate patterns and the thermodynamic control of the ocean-atmosphere system (Bakun and Parrish, 1990;Jablonski and Legey, 2004;Gigliotti et al, 2010;Soares et al, 2011).…”
Section: Introductionmentioning
confidence: 99%